Berlioz in time: from early recognition to lasting renown - Bloom, Peter (Eastman studies in music, 2022)
"This book is a collection of thirteen essays culled from the several books and hundreds of articles I have published and lectures I have given over the years (nearly fifty of them) on the life and work of Hector Berlioz. Organized in a chronological order determined by the essential subject matter of each essay, the book treats in detail some of composer's individual works (the Symphonie fantastique, the Symphonie funèbre et triomphale, Les Nuits d'été, La Mort d'Ophèlie, Les Troyens, Béatrice et Bénédict), some of the composer's relationships with his most famous contemporaries (Franz Liszt, Richard Wagner), some of the composer's most important concerns (his quest for an administrative position; his travels abroad; his fascination with English literature), the composer's most important book (Les Mèmoires d'Hector Berlioz), and some of his most important critics (from shortly after his death, from the twentieth century, and from the early part of the present century). In a brief Prelude, I explain the origins of the book, aspects of my career as a Berliozian, the main theme of much of my research ("politics," loosely defined), and some of the particular concerns to be treated in the texts that follow. In a brief Postlude, I treat the work of Berlioz's important critics based in part on an article of mine that appeared only in French; and I conclude with a note on the current state of Berlioz studies and some thoughts on the needs for the immediate future. Although this is essentially a collection of previously published material, it is my intention seriously to revise it in such a way as to avoid needless repetition over the course of the thirteen chapters, to bring up to date not every last detail but certain crucial matters, and to correct a number of errors and oversights. The material previously published in French and German will, in English, be entirely new"--